Patterns of non-psychotropic medication use and polypharmacy in patients with psychiatric disorders - Yoriyasu Uju; Tetsuto Kanzaki; Riho Hosoi; Seisuke Mimori; Tsuyoshi Takizawa; Tatsuro Hayakawa (Medicine, 2026)
Patients with psychiatric disorders often have various physical diseases that may be associated with an increase in the number of prescribed drugs. Although clinical guidelines addressing antipsychotic polypharmacy are well established, there is limited evidence of non-psychotropic polypharmacy. To elucidate the actual state of inappropriate polypharmacy, this study examined the number and classes of prescribed medicines stratified by age and comorbidities in patients with psychiatric disorders. This cross-sectional study included patients treated in the psychiatric ward of the National Kohnodai Medical Center from April 2015 to March 2016. The study participants included 250 hospitalized patients (150 in the schizophrenia group, 24 in the bipolar affective disorder group, 18 in the depressive disorders group, and others). We examined the number and classes of psychotropic and non-psychotropic drugs stratified by age and the number of comorbidities. Antipsychotics accounted for 47.8% of all the psychotropic medications. Of the total non-psychotropic drugs, 50.2% were used for the treatment of digestive disorders. Age and number of comorbidities were significantly associated with polypharmacy (defined as a prescription with 5 or more drugs) in patients with psychiatric disorders according to logistic regression analysis (odds ratio = 1.66, 95% confidence interval: 1.39–1.97, P < .001 for age; odds ratio = 2.04, 95% confidence interval: 1.58–2.63, P < .001 for comorbidities). Mean non-psychotropic prescription counts rose with both age (0.83 at 10–19, 2.18 at 40–49, 5.80 at >80 years) and comorbidities (0.84 with 0, 3.63 with 3, 6.57 with >5 comorbidities). The mean number of non-psychotropics per patient was linearly related to age range and the number of comorbidities (linear regression coefficient [ b ] = 0.65, P = .0009; b = 0.91, P = .0002, respectively). However, the mean number of psychotropic medications was not related to age or the number of comorbidities. Similar relationships have been observed in patients with schizophrenia. This study highlights the need to monitor non-psychotropic medications to reduce inappropriate polypharmacy among elderly and multimorbid patients with psychiatric disorders.